The Earth: new Techniques for an old Material - Antonio Passaro (Agathón)
The studies that have rediscovered the technique of raw earth constructions in recent years refer to few preexisting in our country and some new architectures. The renewed interest in this practice, if difficult to propose to the large scale of housing, is possible for other uses. Our aim is therefore to move on the analysis of applications and techniques that have been empirically used in the past and have provided satisfactory performances and on the possible achievements that today, with new control possibilities, can be used in the realization of many constructions with a limited environmental impact.